PERSEPSI KONSUMEN TERHADAP KUALITAS PRODUK SABUN LIFEBUOY DI KOTA PONTIANAK - Tripena Susanti; Angelina Fitria Rina Sari (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
The purpose of this study was to determine how the perception and level of consumer buying interest on the quality of Lifebuoy soap products. The variables used are perceptions and consumer buying interest. The number of samples to be used is 100 respondents who are still loyal to using Lifebuoy soap. This research uses qualitative analysis. The result is that consumers' perceptions of the quality of Lifebuoy soap products are good, especially in the variables of performance, features, conformance to specifications, durability, reliability, serviceability, aesthetics and perceived quality. The level of consumer interest in Lifebuoy soap products is also quite large because Lifebuoy soap products can provide the best for consumers who consume them